GENDER PARTICIPATION AND TIME UTILIZATION PATTERN IN EQUINE REARING IN MIDDLE HIMALAYAN REGION OF INDIA - Tanusha; Rupasi Tiwari (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Animal sector is said to be women oriented but one field, Equine rearing, is still predominantly in hands of males. The study was conducted in Chamoli and Uttarkashi districts of Uttarkhand, taking a total of 80 respondents using snowball sampling method. The study discusses about the family labour participation, time utilisation and employment generated through the different activities in rearing of pack animals. The activities were divided as regular and occasional activities and activities like taking animal for grazing, taking animal to work, grooming, treatment, training of animal and marketing were principally the job of males. Taking the animal for grazing consumed most of the time, i.e 4 hours a day. The employment generated for male, female, and child were calculated to be about 289.89, 56.91, and 7.56 man days respectively with a pooled value of 354.66 man days on an average.